Protective Effects of Vitamin C and E in Gentamicin induced Testicular Toxicity in Albino Mice - Bukhari, Anila Shah (International Journal of Pathology, 2020)
Background: Gentamicin is a versatile antibiotic used in wide range of infective diseases including fertilization treatment when there is high leukocyte count in semen. Its therapeutic applications are however hampered due to its nephrotoxicity and ototoxicity. It is also known to cause testicular damage and may lead to infertility. It has been claimed that Vitamin C and E restores sperm motility and fertility in case of gentamicin induced testicular toxicity. Objective: To assess the preventive effect of Vitamin C and E on gentamicin induced testicular toxicity Methods: 30 adult albino male mice were selected and divided into following groups; Group A: control group with no gentamicin and no vitamins. Group B: Only intraperitoneal gentamicin with no vitamins, Group C1: 25 mg intraperitoneal gentamicin with oral 100 ml/kg Vitamin C & E, Group C2: 25 mg intraperitoneal gentamicin with intraperitoneal 100ml/kg Vitamin C & E, Group D1: 50 mg intraperitoneal gentamicin with oral 100 ml/kg Vitamin C & E, Group D2: 50 mg intraperitoneal gentamicin with intraperitoneal 100ml/kg Vitamin C & E. All albino mice were sacrificed after 2 weeks. Testes were preserved in formalin; histological slides were prepared and examined under light microscope. Data was recorded on a Performa and analyzed by SPSS version 20 and t-test was applied for weights of mice and testes. Results:Group A, C and D showed normal testicular morphology while Group B showed decreased diameter of seminiferous tubules, congestion of blood vessels, necrosis, occasional apoptosis, reduced sperm counts and distorted tunica albuginea with a p value of <0.001confirming protective effects of vitamin C & E. Conclusion: Vitamin C and Vitamin E have protective effects on gentamicin induced testicular toxicity in albino mice.